Особенности жития святых Кирилла и Мефодия на основе анализа древнерусских богослужебных текстов - Мельков, Андрей Сергеевич; Melkov A. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статья посвящена важному, но практически неисследованному в науке вопросу, связанному с историей возникновения древних церковных канонов в честь святых Кирилла и Мефодия, а также с церковным почита-нием равноапостольных братьев среди древних славян. Рассмотрены с литературоведческих и лингвистических позиций образцы гимнографического творчества – древние каноны святым Кириллу и Мефодию, которые датирует XII – началом XIII века. На основе анализа этого литургического и текстологического материала, используя археографические приемы и сравнительно-исторический метод, автор последовательно исследует содержание древних церковных канонов и подробно разбирает их текст, сравнивая его с древними житиями святых Кирилла и Мефодия, и приходит к выводу, что тексты канонов святым Кириллу и Мефодию по Сино¬дальному списку имеют следы глубокой древности (конец IX – начало X века). Содержание служб представляет собой исторический материал, тесно перекликающийся с древнейшими житиями славянских просветителей. The article is devoted to an important, but practically unexplored in science question, connected with the history of ancient ecclesiastical canons in honor of Sts. Cyril and Methodius, as well as with the church respect of those Equal-to-the Apostles brothers by ancient Slavs. The author describes some examples of hymnography from the linguistics point of view and literary criticism ancient canons to Sts. Cyril and Methodius, dated by the XII – the beginning of the XIII century. Basing on the analysis of this liturgical and textual material, and using both archaeographic and comparatively-historical methods, the author logically researches the contents of ancient ecclesiastical canons and deciphers their texts in details, comparing them with the ancient lives of Sts. Cyril and Methodius. The author concludes, that the canons’ texts to Sts. Cyril and Methodius according to the Synod list have the roots of deep antiquity (the end of the IX – the beginning of the X centuries). The contents of the services is a kind of historical material, closely connected with the ancient lives of Sts. Slavic enlighteners.
Peculiarities of Sts. Cyril and Methodius’ Lives According to the Analysis of the Ancient Russian Liturgical Texts
Keywords: лингвистика; литературоведение; церковный канон; история; жития святых; археография; сравнительно-исторический метод; язык; текст; linguistics; literary criticism; ecclesiastical canon; history; lives of the Saints; archaeography; comparative-historical method; text; language